(untitled) (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2024)
Young women have a ten times greater risk of suffering from anemia and if it is not handled properly it will reduce the quality of Indonesia’s young generation in the future. If anemia in adolescents continues into adulthood, it will contribute greatly to maternal mortality, premature babies and babies with low birth weight. Based on the results of the 2018 Basic Health Research (Riskesdas), the prevalence of anemia in teenagers is 32%, meaning that 3-4 out of 10 teenagers suffer from anemia. One alternative for meeting iron needs is to consume vegetables that contain iron, one of which is red spinach. This study aims to determine the effectiveness of giving red spinach pudding on the hemoglobin levels of adolescent girls with anemia at the Al Baaqiyatussa’adiyyah Islamic Boarding School in Tembilahan Barat, Indragiri Hilir Regency. This type of research is a Quasi Experiment with a one group pretest posttest research design. The population was all female students with anemia using a total sampling technique and a sample size of 37 respondents. Based on data analysis after giving red spinach pudding, it was found that 19 respondents (51.4%) did not experience anemia and 18 respondents (48.6%) had anemia. The results showed that the average hemoglobin value before being given red spinach pudding was 10.4. The average value after giving red spinach pudding was 12.09 with a p value of 0.000 (p<0.05). Giving red spinach pudding is effective in increasing hemoglobin levels in young women at the Al Baaqiyatussa’adiyyah Islamic Boarding School in Tembilahan Barat, Indragiri Hilir Regency. It is hoped that Islamic boarding schools can provide red spinach pudding snacks for young women so that they can provide adequate nutritional intake to prevent anemia